Critical thinker: visual novel game for building critical thinking skills / Mohamad Amirul Helmi Mohd Jaafar, Muhammad Hamiz Mohd Radzi and Nurshahidatul Hasana Ishak - Mohd Jaafar, Mohamad Amirul Helmi; Mohd Radzi, Muhammad Hamiz; Ishak, Nurshahidatul Hasana (College of Computing, Informatics, and Mathematics, 2024)
Malaysia, amidst the challenges of the modern era, faces a growing demand for individuals equipped with robust critical thinking skills in both industry and education. With the lack of tools/game/platform, the idea of promoting critical thinking is in decline. To address this imperative, the project titled "Critical Thinker: Visual Novel Game for Building Critical Thinking Skills" introduces a game named "Critical Thinker." The game's core objective is to assess and improve users' critical thinking skills through an engaging story- based approach. The usability of this game will also be taken into consideration as it will prove this project’s success. This gamification application, developed through the Game Development Life Cycle (GDLC) and employing the Visual Novel Framework, aims to enhance critical thinking abilities among university students. Leveraging the System Usability Scale for testing, Critical Thinker aspires to be a valuable tool in fostering the intellectual capacities necessary for navigating the complexities of contemporary Malaysian society. The results show a percentage of 73.86%. Hence, the third objective of the Critical Thinker game has been satisfied. The future works of this project would be expanding of the game’s narrative approach, implementing of the inventory system, and enhancing the design of characters and environments.